KOMUNIKASI GURU DALAM PEMBELAJARAN DI MTs AL ITTIHADIYAH PANGKALAN MASYHUR MEDAN - Zunidar Zunidar; Tarmizi Siregar; Henni Damayanti Tambunan (STIT Al-Ittihadiyah Labuhanbatu Utara, 2022)
The purpose of this research is to find out, namely: (1) Communication between teachers and students in the implementation of learning programs in the classroom. (2) communication between students and teachers in implementing learning programs in the classroom, (3) communication between students and students in implementing learning programs in class. This research is using qualitative method. Data collection uses data collection techniques with interviews, observations and documentation regarding communication data in the implementation of the learning program at MTs Al Ittihadiyah Pangkalan Masyhur Medan. To analyze the data used the process of data reduction, data exposure, and drawing conclusions. Furthermore, to ensure the validity of the data and analysis, triangulation techniques were used between interview methods, observation with documentation, and triangulation between informants. There are three kinds of research: First, the communication between teachers and students in the implementation of learning programs shows that in the role of educators and teachers they are very active, open, and persuasive. Second, the implementation of student-teacher communication is generally passive, because in the opening of learning, students only answer what the teacher communicates as a habit in their learning experience as in answering the teacher's questions, and indeed the model, strategy and teaching method are determined. Third, communication between students and students in the implementation of the learning program is carried out formally when the teacher teaches by using the lecture method interspersed with the use of questions and answers, the question and answer method, which is arranged by the teacher, or the discussion method.